2011
DOI: 10.1007/s00414-011-0634-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of focal myocardial inflammation in sudden unexpected cardiac and noncardiac deaths—A clinicopathological study

Abstract: The significance of focal myocardial inflammation in sudden death is poorly understood, because there are few studies addressing its frequency in noncardiac and cardiac arrhythmic deaths. We prospectively assessed inflammation in 384 consecutive hearts seen in consultation from a single medical examiners' office. Hearts were received intact and sectioned uniformly in five areas and reviewed histologically by a single pathologist. Intrinsic inflammatory diseases of the myocardium were excluded. Infiltrates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The so-called 'Dallas criteria', proposed in 1986, are of limited use in forensic application because they were formulated for endomyocardial biopsy, not autopsy, diagnosis. 36 A correct post mortem approach presents considerable difficulties of interpretation. 37,38 Some authors pointed out the possibility of an overestimation in the histological diagnosis of myocarditis: focal inflammatory infiltrates, also with marked myocytolysis, may represent an incidental finding at autopsy in patients who died from violent causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called 'Dallas criteria', proposed in 1986, are of limited use in forensic application because they were formulated for endomyocardial biopsy, not autopsy, diagnosis. 36 A correct post mortem approach presents considerable difficulties of interpretation. 37,38 Some authors pointed out the possibility of an overestimation in the histological diagnosis of myocarditis: focal inflammatory infiltrates, also with marked myocytolysis, may represent an incidental finding at autopsy in patients who died from violent causes.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Some authors pointed out the possibility of an overestimation in the histological diagnosis of myocarditis: focal inflammatory infiltrates, also with marked myocytolysis, may represent an incidental finding at autopsy in patients who died from violent causes. 36,39 In order to have a correct diagnostic classification, Casali et al 40 proposed a routine application of a careful histological mapping from the whole heart (analysis of at least 20 slides in the authors' opinion) and a careful anamnestic investigation for an appropriate integration of anatomo-pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Current concept of focal myocarditis as an incidental finding is not well established. It is known that small inflammatory foci with necrosis occurs in less than 5% of the autopsied hearts, and is likely a contributing factor in cases od unexplained sudden death (14). However, not all focal myocarditis result in unexplained sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lymphocytic infiltrates are present in the myocardial interstitium of healthy subjects (Fineschi et al 2006). To achieve a better understanding of the significance of focal myocardial inflammation in sudden death, Zhang et al (2011) recently assessed inflammation in 384 consecutive hearts in which intrinsic inflammatory diseases of the myocardium were excluded. Infiltrates were classified as lymphocytic without necrosis, lymphocytic with myocyte necrosis and eosinophilic.…”
Section: Lymphocytic Myocarditismentioning
confidence: 99%
“…The authors concluded that incidental cardiac inflammatory infiltrates without necrosis are not uncommon, but focal myocarditis, defined as inflammation with necrosis, occurs in about 5% of hearts, and may be considered a possible contributory factor. Incidental infiltrates are common in patients on medications, especially antibiotics (Zhang et al 2011).…”
Section: Lymphocytic Myocarditismentioning
confidence: 99%